Eco-friendly extraction technologies: A comprehensive review of modern green analytical methods - Binoy Varghese Cheriyan; Karthik K Karunakar; Ragavendran Anandakumar; Akshaya Murugathirumal; Abinaya Senthil kumar (Sustainable Chemistry for Climate Action)
The current review explores new developments in green analytical chemistry with an emphasis on eco-friendly extraction methods. The study covers solid-phase microextraction (SPME), stir bar sorptive extraction (SBSE), supercritical fluid extraction (SFE), microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE), ionic liquid-based extraction, pressurised liquid extraction (PLE), and Fabric Phase Sorptive Extraction (FPSE). These approaches provide substantial enhancements in efficiency, selectivity, and environmental sustainability as compared to conventional extraction methods. This study examines the fundamental concepts, instrumentation, and applications of each method, emphasising their contributions to the reduction of solvent consumption, waste minimisation, and enhancement of analytical performance in diverse domains such as environmental monitoring, food analysis, and pharmaceutical research. This paper discusses the current constraints associated with matrix effects, equipment expenses, and method optimization. The publication provides details on recent advancements in the particular domain, such as novel sorbent materials, hybrid systems, and the integration of multiple methodologies. Within our research, we emphasized the prospective developments related to the use of more environmentally friendly materials, more automation, and real-time in situ analytics. The present study emphasizes green extraction techniques as the central driving force behind sustainable analytical chemistry and highlights their potential to revolutionize the domain of sample preparation in analytical chemistry.